2016
DOI: 10.1159/000448597
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Cerebrovascular Pathology with Patients Suffering from Ph-Negative Myeloproliferative Disease

Abstract: Background: Disturbances of microcirculation play a significant role in the development and progression of both acute and chronic cerebrovascular diseases (CVD) and may be associated with different hemogram abnormalities. One of the reasons of the prothrombogenic state of the endothelium is the increase in the number of blood corpuscles leading to (non-Ph) myeloproliferative disorders (MPD) including essential thrombocythemia (ET), polycythemia vera (PV), and primary myelofibrosis (PM). Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Kato et al reported that of 10 consecutive patients with ischaemic stroke with ET analysed in their study, 2 (20%) had LCAD-related stroke 4) . Tanashyan et al reported that 21% of the young (≤ 58 years old) patients with MPNs (21/102) in their study experienced acute cerebrovascular events, and 8 of them (38%) had thrombotic occlusion of one of the internal carotid arteries 12) . In their prospective study, Nagai et al identified large vessel involvement in 5 of 23 (22%) patients with MPNs with ischaemic stroke 3) .…”
Section: Demographic Characteristics Of the Patients With Myeloprolif...mentioning
confidence: 87%
“…Kato et al reported that of 10 consecutive patients with ischaemic stroke with ET analysed in their study, 2 (20%) had LCAD-related stroke 4) . Tanashyan et al reported that 21% of the young (≤ 58 years old) patients with MPNs (21/102) in their study experienced acute cerebrovascular events, and 8 of them (38%) had thrombotic occlusion of one of the internal carotid arteries 12) . In their prospective study, Nagai et al identified large vessel involvement in 5 of 23 (22%) patients with MPNs with ischaemic stroke 3) .…”
Section: Demographic Characteristics Of the Patients With Myeloprolif...mentioning
confidence: 87%
“…Одним из основных клинических проявлений данных нозологических форм Ph-негативных МПЗ являются тромбозы (как артериальные, так и венозные) различной локализации, которые встречаются до 40% случаев [4]. В ряде исследований показана ассоциация цереброваскулярной патологии с МПЗ [5], причем важной особенностью нередко является развитие острых нарушений мозгового кровообращения (ОНМК) как дебюта -первого клинического проявления «асимптомного» МПЗ [6]. Возникновение ОНМК возможно также во время специфической циторедуктивной, антиагрегантной терапии основного гематологического заболевания.…”
unclassified